Indonesia PENGARUH PEMANASAN MEDIA NA - Erlinawati Sukedi; Fitriana Fitriana; Asri Jumadewi (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
The Microbiology Laboratory at the Department of Medical Laboratory Technology, Poltekkes Kemenkes Aceh, often uses Nutrient Agar (NA) media to count the total number of bacteria in various bacteriology practicums. This media, after being made and cooled to harden, is stored in a refrigerator at 2-8°C for 1-2 weeks. Before use, the media must be reheated at 100°C to thaw it. This process is often done repeatedly to save labor and facilities in the laboratory. However, repeated heating of NA media is thought to lower the pH of the media and reduce the number of bacterial colonies that grow, potentially affecting the accuracy of microbiological test results. Therefore, this study was conducted to determine the extent to which repeated heating of NA media affects the pH and growth of bacterial colonies. Experimental method with a completely randomized design. Data were collected through repeating the heating of NA media 4 times, and the pH and number of colonies growing were measured after certain time intervals until heating was done 5 times. The results showed that repeated heating of NA media affected pH and bacterial growth. The more often the media is heated, the lower the pH of the media, and the fewer bacterial colonies grow. Repeated heating of Nutrient Agar (NA) media has an effect on bacterial TPC or the amount of Escherichia coli bacterial growth.